Konsumsi pangan dan skor pola pangan harapan (PPH) dengan prevalensi stunting di Provinsi Aceh (Data Susenas dan PSG tahun 2016) - Suryana Suryana; Roudza Roudza; Alfridsyah Alfridsyah (AcTion: Aceh Nutrition Journal, 2018)
Stunting in toddlers is one of the big problems that can threaten the development of the Quality of Human Resources, that can have an impact on national development. Quality human resources can be obtained by consuming adequate food, both in quantity, quality and balance. Associated with the problem of stunting food consumption in Aceh Province based on the Score Desirable Dietary Pattern as DDP is still less than DDP ideal is 70.0. This study aims to determine the association of food consumption and the Hope Food Pattern score with the prevalence of stunting in Aceh Province. This research is a descriptive analytic with the Cross-Sectional. Study design. The study used secondary data, National Census data analysis and Nutritional Status Monitoring 2016. The analysis used is a regression. The results showed that the average energy and protein consumption in households in Aceh Province was 2.276 kcal of energy and 65,21 grams of protein. The average energy and protein consumption are in the normal category of 105,8% (energy) and 114,0% (protein). The diversity of food consumption has not been varied enough based on the average score in Aceh Province is 77,8. Stunting is a public health problem with a mild problem category known from the average value of stunting prevalence of 26,3%. There was no relationship from AKE (p= 0,430), PPA (p= 0,274) and PPH score (p= 0,259) with stunting prevalence based on District / City in Aceh Province in 2016. The conclusion is There was no significant relationship between stunting and Energy Adequacy Rate (AKE), Protein Adequacy Rate (PPA), and Score DDP.